Sri Lanka : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper on Sri Lanka provides background information on economic developments during 1995 and the first half of 1996 and on key policy issues in the current setting. The paper notes that the economic situation has deteriorated on a number of fronts-inflation has risen; investment and growth have slowed; and the external current account deficit is large while foreign investment flows have fallen significantly. The influence of various factors on Sri Lanka's longer-term growth performance is discussed. The implications of structural reforms for investment and growth are also examined.